1986
DOI: 10.1128/aac.30.2.270
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of experimental cerebral nocardiosis with imipenem, amikacin, trimethoprim-sulfamethoxazole, and minocycline

Abstract: A mouse model of cerebral nocardiosis was used to determine relative antibiotic efficacy by reducing bacterial colony counts per gram of brain tissue. The antimicrobial agents employed were demonstrated in vitro to be inhibitory to most strains of Nocardia asteroides at very low concentrations. The agents used in this study were imipenem-cilastatin, amikacin, trimethoprim-sulfamethoxazole, and minocycline. Antibiotics were administered every 4 h for 72 h before animal sacrifice. Bacterial colony counts were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
4

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 21 publications
2
46
0
4
Order By: Relevance
“…In addition, in other experimental studies that used antimicrobial combinations that have been shown to demonstrate synergy in vitro, imipenem-amikacin, imipenem-cefotaxime, and amikacin-cefotaxime were found to be efficacious (42,192,195). In a study of central nervous system nocardiosis, these combinations were also proven to be statistically superior to single-agent therapy (193 (23). Also, these authors were clearly able to distinguish the genus Actinomadura from N. dassonvillei by using numerical data.…”
Section: Histopathologymentioning
confidence: 70%
See 1 more Smart Citation
“…In addition, in other experimental studies that used antimicrobial combinations that have been shown to demonstrate synergy in vitro, imipenem-amikacin, imipenem-cefotaxime, and amikacin-cefotaxime were found to be efficacious (42,192,195). In a study of central nervous system nocardiosis, these combinations were also proven to be statistically superior to single-agent therapy (193 (23). Also, these authors were clearly able to distinguish the genus Actinomadura from N. dassonvillei by using numerical data.…”
Section: Histopathologymentioning
confidence: 70%
“…Antimicrobial agents that may be of clinical benefit include broad-spectrum cephalosporins, fluoroquinolones (166,568), clindamycin, erythromycin, ampicillin, aminoglycosides (in particular, amikacin), tetracyclines (including minocycline), and imipenem (42,128). Broad-spectrum cephalosporins such as cefotaxime have also been shown to be very active in vitro and successful in the therapy of experimental infections (570 (193,194). In addition, in other experimental studies that used antimicrobial combinations that have been shown to demonstrate synergy in vitro, imipenem-amikacin, imipenem-cefotaxime, and amikacin-cefotaxime were found to be efficacious (42,192,195).…”
Section: Histopathologymentioning
confidence: 99%
“…The investigators found that treatment with either amikacin or sulfonamides for 2 to 3 weeks increased the rate of resolution of infection (209). Later, Gombert and colleagues used a mouse model of cerebral nocardiosis to evaluate the relative efficacy of four antimicrobials, i.e., TMP-SMX, amikacin, imipenem, and minocycline (68,69). Of the four agents tested, amikacin and imipenem were found to be the most effective agents against a single strain of N. asteroides complex (which in neither this study nor the previously mentioned study was identified to species using modern taxonomic methods) (68,69).…”
Section: Downloaded Frommentioning
confidence: 99%
“…There are also patients who develop side effects, necessitating the withdrawal of these compounds. Other antimicrobial agents, such as amikacin and imipenem, as well as several newer beta-lactams, have shown activity against N. asteroides in vitro, as well as in an experimental model of cerebral nocardiosis (6,7,9,10). There are also reports of successful therapy with agents other than the sulfa compounds (3).…”
mentioning
confidence: 99%